2015
DOI: 10.1098/rsbl.2015.0259
|View full text |Cite
|
Sign up to set email alerts
|

Tracheal compression in pupae of the beetleZophobas morio

Abstract: Insects that are small or exhibit low metabolic rates are considered to not require active ventilation to augment diffusive gas exchange. Some pupae with low metabolic rates exhibit abdominal pumping, a behaviour that is known to drive tracheal ventilation in the adults of many species. However, previous work on pupae suggests that abdominal pumping may serve a non-respiratory role. To study the role of abdominal pumping in pupa of the beetle Zophobas morio, we visualized tracheal dynamics with X-rays while si… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 20 publications
(21 citation statements)
references
References 12 publications
(22 reference statements)
0
21
0
Order By: Relevance
“…The tracheal system DLTs of two different mosquito larvae were compared using SR‐μCT. Synchrotron X‐ray imaging technique has been employed to investigate insect breathing (Greenlee et al, ; Pendar, Kenny, & Socha, ). In this study, we found that the thorax and abdominal segments differed remarkably between the two mosquito larvae.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The tracheal system DLTs of two different mosquito larvae were compared using SR‐μCT. Synchrotron X‐ray imaging technique has been employed to investigate insect breathing (Greenlee et al, ; Pendar, Kenny, & Socha, ). In this study, we found that the thorax and abdominal segments differed remarkably between the two mosquito larvae.…”
Section: Discussionmentioning
confidence: 99%
“…The rhythmic tracheal movement during respiration might be induced by combined effects of the macroscale geometry, microscale organization, and mesoscale heterogeneity (Webster, Socha, Teresi, Nardinocchi, & De Vita, 2015). The emission rate of CO 2 is affected by the intratracheal CO 2 level and the opening area of spiracles (Pendar et al, 2015). The dynamic behavior of spiracles could be affected by concentrations of O 2 and CO 2 (Burkett & Schneiderman, 1974).…”
Section: Analysis Of Breathing Behavior Using Dltsmentioning
confidence: 99%
See 1 more Smart Citation
“…The abdominal pump has most often been implicated as a mechanism of active respiration, but abdominal pumping does not always result in respiratory airflow. For example, in a study of Zophobas morio beetle larvae 7 , more than half (63.7%) of the observed abdominal pumping events occurred while the spiracles were closed, resulting in no tracheal compressions producing advection and no external gas exchange. Similar results were found in studies of adult Schistocerca gregaria grasshoppers 8 and Bombus terrestris bumblebees 9 , in which individuals exhibited periods of abdominal pumping with no CO 2 emission ranging in duration from 2 to 30 minutes.…”
Section: Introductionmentioning
confidence: 99%
“…Non‐invasive X‐ray computed tomography (=CT) methods have recently become popular for studying animal morphology and development (e.g. Hammel et al ., ; Friedrich et al ., ; Handschuh et al ., ; Blanke et al ., ; Pendar et al ., ; Weihmann et al ., ). This is because, in contrast to other imaging techniques, CT has the advantage of simultaneously accessing internal and external anatomical details of virtually any organism.…”
Section: Introductionmentioning
confidence: 95%